1997
DOI: 10.1016/s0014-5793(97)00005-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium mediates the activation of the inhibitory current induced by odorants in toad olfactory receptor neurons

Abstract: In toad olfactory neurons, a putrid odorant mixture inducing inhibitory responses increases Ca 2+ -activated K + conductance, developing a hyperpolarizing receptor potential. Removal of extracellular Ca 2+ or exposure to nifedipine reversibly reduced the inhibitory response, suggesting that odorants induce a Ca 2+ influx. We show evidence for an odorant-induced Ca 2+ current. Using confocal microscopy, it is shown that odorants induce a nifedipine-sensitive elevation of Ca 2+ in the apical end of the cell. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…It should be noted that a small percentage of ORNs both in amphibians and rodents sometimes exhibit inhibitory odor responses (Duchamp-Viret et al 1999;Morales et al 1997). Such inhibitory responses were also seen infrequently in our experiments (unpublished observations).…”
Section: Discussionsupporting
confidence: 66%
“…It should be noted that a small percentage of ORNs both in amphibians and rodents sometimes exhibit inhibitory odor responses (Duchamp-Viret et al 1999;Morales et al 1997). Such inhibitory responses were also seen infrequently in our experiments (unpublished observations).…”
Section: Discussionsupporting
confidence: 66%
“…The Ca 2+ passing through these channels in turn activates Ca 2+ -activated Cl -channels, which amplifies depolarization in ORNs (21) 2+ channels have been shown to be primarily present on the soma and the proximal dendrite (31). It has been reported that a high concentration of nifedipine (20 mM) inhibited the Ca 2+ signals in response to odorants (22). However, several Ca 2+ channel inhibitors including nifedipine at high concentrations are reported to inhibit nucleotide-gated channels as well (23,24).…”
Section: +mentioning
confidence: 99%
“…However, studies with gene-targeted mice deficient for adenylyl cyclase III, the CNGA2 subunit of the CNG channel and G olf (Belluscio et al 1998;Brunet et al 1996;Wong et al 2000) have called into question the validity of the results of the biochemical experiment within the context of intact OSNs. Indeed, subsequent publications from the group of Bacigalupo do not make specific claims on the identity of the second messenger involved in inhibitory odorant responses (Morales et al 1997;Sanhueza et al 2000).…”
Section: Camp-gated Opening Of the Cng Channel Mediates Both Depolarimentioning
confidence: 99%